Inducing liquid crystallinity in dilute MXene dispersions for facile processing of multifunctional fibers. Issue 9 (8th February 2022) - Usman, Ken Aldren S.; Zhang, Jizhen; Qin, Si; Yao, Ya; Lynch, Peter A.; Mota-Santiago, Pablo; Naebe, Minoo; Henderson, Luke C.; Hegh, Dylan; Razal, Joselito M.
Abstract : The addition of CNCs into MXene dispersions enables LC-MXene phases at lower critical transition concentrations, allowing wet spinning of fibers using previously unspinnable concentrations of MXene. Abstract : The liquid crystal (LC) phases of two-dimensional (2D) transition metal carbides/nitrides (MXenes) have enabled the production of their unique macro-architectures with an ordered microstructure and enhanced properties. However, LC phases in additive-free MXene dispersions are known to occur above relatively high sheet size and concentration thresholds, which can be difficult to obtain and process. Easily prepared non-LC MXene dispersions composed of small sheets at low concentrations on the other hand, do not possess adequate rheological properties to form desired macro-architectures. Here, we report that LC phases in dilute MXene dispersions can be induced by adding cellulose nanocrystals (CNCs), even at concentrations significantly below its own LC threshold. The favorable mutual interaction lowers the concentration and size threshold for MXene solution processing into robust superior macro-architectures, and improves the properties of LC-MXene fibers produced at conventional concentrations (∼30 mg mL −1 ). As an example, fibers wet-spun from 10 mg mL −1 LC CNC–MXene containing 75% MXene (M75 ), exhibit high tensile strength (∼60 MPa), conductivity (∼3000 S cm −1 ), and volumetric capacitance (∼950 F cm −3 ), in contrast to 10 mg mL −1 pure MXene (M100 ), which was unspinnable. The synergistic improvements brought by CNCs on LC formation may be extended to mixed dispersions of other nanomaterials and is anticipated to further broaden the array of solution processing of MXenes into functional architectures and devices.